Infant malnutrition and obesity in three population-based birth cohort studies in Southern Brazil: trends and differences Desnutrição e obesidade infantis em três coortes de nascimentos no Sul do Brasil: tendências e diferenças - Aluísio J. D. Barros; Cesar G. Victora; Iná S. Santos; Alicia Matijasevich; Cora L. Araújo; Fernando C. Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The aim of this study was to compare the evolution of nutritional deficits and overweight in one-year-old children from three birth cohorts started in 1982, 1993 and 2004 in Pelotas, Southern Brazil. Samples from the 1982 and 1993 cohorts and all children from 2004 were weighed and measured, and their mothers interviewed. Anthropometric deficits and overweight were assessed using both NCHS and WHO growth standards. A comparison of the existence of nutritional deficits showed that, after a decline between 1982 and 1993, its prevalence stabilized between 1993 and 2004. Across the whole period, a decrease in all deficits was observed. Obesity, on the other hand, increased. A deficit in the ratio of body length to age was found to be strongly associated with family income. The group with income below one minimum wage was the only to present a significant reduction of stunting during the study period. The most significant improvements in the reduction of nutritional deficits occurred in the first half of the study period, while social differentials remained. Fighting malnutrition is still necessary among the 40% of the population considered poor, and must be accompanied by efforts to combat overweight which is being observed in all social strata. O estudo teve como objetivo comparar a evolução dos déficits nutricionais e sobrepeso em crianças de um ano, com base em três coortes de nascimentos iniciadas em 1982, 1993 e 2004 em Pelotas, Rio Grande do Sul, Brasil. Amostras das coortes de 1982 e 1993 e todos as crianças da coorte de 2004 foram pesadas e medidas, e suas mães foram entrevistadas. Déficits antropométricos e sobrepeso foram analisados utilizando os padrões de crescimento definidos pelo NCHS e OMS. A comparação dos déficits nutricionais mostrou que, depois de declinar entre 1982 e 1993, a prevalência se estabilizou entre 1993 e 2004. Durante o período inteiro, foi observada uma diminuição em todos os déficits. Inversamente, houve um aumento na obesidade. Baixa estatura para a idade esteve fortemente associada com renda familiar. O grupo de renda familiar abaixo de um salário mínimo foi o único que mostrou uma redução significativa em baixa estatura para idade durante o período estudado. Houve melhorias importantes na redução dos déficits nutricionais na primeira metade do período de estudo, embora ainda persistam desigualdades sociais. Combater a desnutrição ainda é necessário nos 40% mais pobres da população, em paralelo com a luta contra o sobrepeso, que vem sendo observado em todas as classes sociais.